Mathematical geosciences : hybrid symbolic-numeric methods /: hybrid symbolic-numeric methods. ([2018]) - Awange, Joseph L, 1969-; Völgyesi, Lajos; Paláncz, Béla, 1944-; Lewis, Robert H, 1949-
No abstract available